A Qualitative Exploration into How Teachers Understand and Practice Forgiveness - Corinne DenHartog (MDPI AG, 2024)
Forgiveness, though hard for many to simply define in concrete terms, is not necessarily a foreign concept or practice for the average individual. In an attempt to further understanding of forgiveness, the present study gathered the thoughts, opinions, and experiences of a specific community of individuals, public school teachers. Using a series of six focus group interviews, analysis of data produced insights and conclusions related to how teachers understand forgiveness in theory and practice, how they practice forgiveness within their jobs, and their thoughts on forgiveness or virtue education within schools. Thematic analysis is presented with quotational support and a discussion of application to both forgiveness theory and future forgiveness education pursuits is offered in summation. Due to the many mental, emotional, and physical health benefits associated with forgiveness, the value of exploring forgiveness and forgiveness education is readily evident. This study provides a glimpse into the experiences of a community of individuals who practice forgiveness regularly within the context of their jobs as public school educators.